2021
DOI: 10.1093/aob/mcab043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and practical use of self-compatibility in outcrossing grass species

Abstract: Background Self-incompatibility (SI) systems prevent self-fertilisation in several species of Poaceae, many of which are economically important forage, bioenergy and turf grasses. SI ensures cross-pollination and genetic diversity but restricts the ability to fix useful genetic variation. In most inbred crops, it is possible to develop high performing homozygous parental lines by self-pollination which then enables the creation of F1 hybrid varieties with higher performance, a phenomenon know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 167 publications
1
6
0
Order By: Relevance
“…Although, self-incompatibility ensures cross-pollination and genetic diversity, it makes the xing of useful genes di cult (Cropano et al, 2021). In addition, self-compatible clones will not need pollinators when used to establish plantations (Munoz-Sanz et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Although, self-incompatibility ensures cross-pollination and genetic diversity, it makes the xing of useful genes di cult (Cropano et al, 2021). In addition, self-compatible clones will not need pollinators when used to establish plantations (Munoz-Sanz et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of a functional gene copy of an SI determinant, disrupting the initial self-recognition process, is not the only source of self-compatibility ( Do Canto et al 2016 ). Similarly, a recombination event between the SI determinants, silencing of the SI determinants, or a mutation interfering with the downstream cascade of SI unlinked to the S - and the Z -locus represent other sources of self-compatibility ( Do Canto et al 2016 ; Cropano et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that environmental changes sometimes induce temporal pollination‐type conversions (Kalisz & Vogler, 2003; Kalisz et al, 2004). Furthermore, it has been pointed out that converting the pollination type from cross‐pollination to self‐pollination could provide an advantage from an agricultural viewpoint because species that can be maintained and propagated by self‐pollination are easily stored and distributed as seeds (Cropano et al, 2021; Yang & Mackenzie, 2019). In this study, we showed that the reduction in EPFL6 activity causes the failure in self‐pollination at a cool temperature (Figure 1).…”
Section: Discussionmentioning
confidence: 99%